Serious Video Games: Angels or Demons in Patients With Attention-Deficit Hyperactivity Disorder? A Quasi-Systematic Review - Rodrigo-Yanguas, María; González-Tardón, Carlos; Bella-Fernández, Marcos; Blasco-Fontecilla, Hilario (Frontiers in Psychiatry, 2022)
Objective: To carry out a quasi-systematic review of the use of serious video games for health as a cognitive rehabilitative tool in patients diagnosed with attention deficit hyperactivity disorder. METHOD: A quasi-systematic review of serious video games used as an evaluative and rehabilitative tool in patients with ADHD was conducted. It included behavioral patterns in the use of video games and addiction problems in this population. For its elaboration the PRISMA GUIDES were followed. The search was carried out in three PubMed databases, MEDLINE, PsycInfo using the keywords: [game OR serious game OR computer game) AND (psychotherapy OR rehabilitation OR intervention OR mental disorders) AND (adhd)], ["(adhd) AND (Video game addiction)] All articles written in English, Spanish or Portuguese from January 1970 to June 2021 were included: those in which reference was made to the use of video games and /or new technologies as a therapeutic and evaluative tool in children and adults diagnosed with ADHD, as well as those that referred to behavioural and clinical patterns in the use of video games. RESULTS: We found 605 articles of which 128 were reviewed (44 observational studies, 26 quasi-experimental studies, 26 experimental studies, 8 systematic reviews, 9 narrative texts, 6 case reports, 7 pilot studies, 8 systematic reviews and 2 meta-analyses). Serious video games can be used to ameliorate ADHD symptoms while improving adherence to treatment. Some serious video games show high accuracy properties assessing ADHD features. CONCLUSIONS: Serious video games for health are increasingly being used as a cognitive rehabilitation tool in patients with attention deficit hyperactivity disorder (ADHD).